Self-reported sensory responsiveness patterns in typically-developing and early-onset schizophrenia adolescents: Its relationship with schizotypal and autistic traits. (December 2020) - Zhou, Han-yu; Yang, Han-xue; Cui, Xi-long; Shi, Li-juan; Gong, Jing-bo; Lui, Simon S.Y.; Cheung, Eric F.C.; Watanabe, Katsumi; Chan, Raymond C.K.
Abstract: Altered behavioural responses to sensory stimuli, including both hypo- and hyper-reactivity, have been found in individuals with schizophrenia. However, how specific sensory responsiveness patterns are associated with symptomatology of schizophrenia remains largely unknown. The present study aimed to examine sensory responsiveness in typically-developing (TD) adolescents ( n = 98) and adolescents with early-onset schizophrenia (EOS) ( n = 29) and investigate the relationship between schizotypal traits and sensory responsiveness patterns. All participants completed the Adult/Adolescent Sensory Profile (AASP), the Schizotypal Personality Questionnaire (SPQ) and the Autism Spectrum Quotient (AQ). Results showed that higher levels of hypersensitivity and hyposensitivity coexisted in EOS patients and were correlated with positive and negative symptoms of schizophrenia. Atypical sensory experiences except for sensory seeking were found to be positively correlated with higher levels of schizotypal traits regardless of diagnostic status. Moreover, the strength and pattern of such correlations were comparable in both EOS and TD groups. This study also provided evidence that higher levels of autistic traits would intensify the positive correlation between schizotypal traits and sensory responsiveness abnormalities, suggesting an additive effect of co-occurring schizotypal and autistic traits on atypical sensory experiences. These findings extend previous research by depicting sensory responsiveness patterns in younger populations with schizophrenia, and may have implications for future development of sensory-related interventions in clinical settings.